2006
DOI: 10.1016/j.devcel.2006.04.001
|View full text |Cite
|
Sign up to set email alerts
|

SynMuv Genes Redundantly Inhibit lin-3/EGF Expression to Prevent Inappropriate Vulval Induction in C. elegans

Abstract: Activation of EGFR-Ras-MAPK signaling in vulval precursor cells (VPCs) by LIN-3/EGF from the gonad induces vulval development in C. elegans. The prevailing view is that LIN-3 overcomes an "inhibitory signal" from the adjacent hyp7 hypodermal syncytium. This view originated from observations indicating that inactivation of functionally redundant Synthetic Multivulva (SynMuv) genes in hyp7 can activate EGFR-Ras-MAPK signaling in the VPCs. Many SynMuv genes encode transcription and chromatin-associated factors, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
129
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(140 citation statements)
references
References 39 publications
11
129
0
Order By: Relevance
“…Adult or L4 worms were used for counting intestinal nuclei in strains containing elt-2::gfp/LacZ reporter. RNAi by feeding was performed as described (7 13-dependent genes that we tested by real-time RT-PCR, sod-3, had an increased expression in unc-13(e1091) background compared with wild type (data not shown). However, its expression was even higher in the lin-35unc-13 strain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult or L4 worms were used for counting intestinal nuclei in strains containing elt-2::gfp/LacZ reporter. RNAi by feeding was performed as described (7 13-dependent genes that we tested by real-time RT-PCR, sod-3, had an increased expression in unc-13(e1091) background compared with wild type (data not shown). However, its expression was even higher in the lin-35unc-13 strain.…”
Section: Methodsmentioning
confidence: 99%
“…The C. elegans Rb protein LIN-35 represses inappropriate transcription of germline-specific genes (12) and growth factors (13) in differentiated somatic cells and functions redundantly with other transcriptional repressors (14). Also, lin-35 mutants are more sensitive to exogenous RNAi than wild-type worms (11,15).…”
mentioning
confidence: 99%
“…In this article, 1 we show that these putative class C synMuv genes are not distinct from and should be considered class B synMuv genes. The gene lin-3, which encodes the EGF-like ligand of the RTK/Ras pathway required for the specification of vulval cell fates (Hill and Sternberg 1992), is an apparent direct or indirect transcriptional target of at least some synMuv genes (Cui et al 2006). Given this observation and the molecular nature of many synMuv proteins, the synMuv proteins likely act as transcriptional repressors to prevent the ectopic expression of the RTK/Ras pathway ligand LIN-3 and in this way prevent ectopic vulval induction.…”
Section: G Lobal Analyses Of Loss-of-function Mutants Havementioning
confidence: 99%
“…The penetrances of synMuv vulval phenotypes correlate with the level of lin-3 mRNA expression: Cui et al (2006) reported that the lin-3 gene, which encodes the EGF ligand of the Ras pathway is a transcriptional target of some synMuv proteins. Three double mutants carrying a class A and a class B synMuv mutation had increased lin-3 EGF mRNA levels.…”
Section: Most Class B-b Double Mutants Do Not Have Muv Phenotypesmentioning
confidence: 99%
“…Constitutively active Wnt signal transduction causes VPCs that normally adopt the 3°fate to be ''overinduced'' (as assessed by ectopic invaginations), even when EGFR-Ras-MAPK activity is reduced (28). However, a situation in which Wnt signaling is artificially activated may be misleading as an indication of its normal role; a cautionary tale is afforded by the effect of removing SynMuv gene activity, which creates an artificial signaling event (32). In addition, lin-39 activity both prevents fusion and promotes division (4); thus, it is conceivable that abnormally high lin-39 levels in pry-1 mutants (perhaps in combination with other ectopically elevated factors) could cause spurious division so that P4.p or P8.p may divide ectopically without having responded to normal patterning signals.…”
Section: Lin-3/egf Signaling: Maintaining Competence Versus Initiatinmentioning
confidence: 99%